How do you solve 6( m - 2) + 14= 3( m + 2) - 10?

2 Answers
Apr 8, 2018

m=2/3

Explanation:

Expand the brackets on both sides:

6m-12+14=3m+6-10

Take away the 3m from the right side of the equation:

3m-12+14=+6-10

Work out additions and subtractions:

3m+2=+4

Take away the +2:

3m=2

Divide both sides by 3:

(3m)/3=2/3

So:

m=2/3

Apr 8, 2018

m=2/3

Explanation:

So we just multiply the number before the bracket with all the numbers in the bracket. Simple algebra.

6(m-2)+14=3(m+2)-10
6m-12+14=3m+6-10
3m -12 +14 =6 - 10
3m =-6+10 +12 -14
3m=22-20 = 3m=2
(3m)/3 =2/3
m = 2/3